2002
DOI: 10.1515/bc.2002.196
|View full text |Cite
|
Sign up to set email alerts
|

Amylin-Induced Cytotoxicity Is Associated with Activation of Caspase-3 and MAP Kinases

Abstract: Nanomolar concentrations of human amylin promote death of RINm5F cells in a time- and concentrationdependent manner. Morphological changes of chromatin integrity suggest that cells are predominantly undergoing apoptosis. Human amylin induces significant activation of caspase-3 and strong and sustained phosphorylation of stress-activated protein kinases, c-Jun N-terminal kinase (JNK) and p38, that precedes cell death. Extracellular signal-regulated kinase (ERK) activation was not concomitant with JNK and/or p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…Previous in vitro studies have suggested different mechanisms for hIAPP toxicity, including formation of non-selective ion channel-like structures [19][20][21][22][23], activation of the caspase pathways [24,25], and interaction of hIAPP fibrils with components of beta cell membranes, such as heparan sulphate proteoglycan [26,27] or touch receptors [28]. It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies have suggested different mechanisms for hIAPP toxicity, including formation of non-selective ion channel-like structures [19][20][21][22][23], activation of the caspase pathways [24,25], and interaction of hIAPP fibrils with components of beta cell membranes, such as heparan sulphate proteoglycan [26,27] or touch receptors [28]. It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l).…”
Section: Introductionmentioning
confidence: 99%
“…
OBJECTIVES-We sought to 1) Determine whether solublemisfolded amylin or insoluble-fibrillar amylin may cause or result from diabetes in human amylin transgenic mice and 2) determine the role, if any, that insulin resistance might play in these processes.RESEARCH DESIGN AND METHODS-We characterized the phenotypes of independent transgenic mouse lines that display pancreas-specific expression of human amylin or a nonaggregating homolog, [ 25,28,29 Pro]human amylin, in an FVB/n background.RESULTS-Diabetes occurred in hemizygous human amylin transgenic mice from 6 weeks after birth. Glucose tolerance was impaired during the mid-and end-diabetic phases, in which progressive ␤-cell loss paralleled decreasing pancreatic and plasma insulin and amylin.
…”
mentioning
confidence: 99%
“…Even in advanced diabetes, islets lacked amyloid deposits. In islets from nontransgenic mice, glucagon and somatostatin cells were present mainly at the periphery and insulin cells were mainly in the core; in contrast, all three cell types were distributed throughout the islet in transgenic animals.[ 25,28,29 Pro]human amylin transgenic mice developed neither ␤-cell degeneration nor glucose intolerance.CONCLUSIONS-Overexpression of fibrillogenic human amylin in these human amylin transgenic mice caused ␤-cell degeneration and diabetes through mechanisms independent from both peripheral insulin resistance and islet amyloid. These findings are consistent with ␤-cell death evoked by misfolded but soluble cytotoxic species, such as those formed by human amylin in vitro.…”
mentioning
confidence: 99%
See 2 more Smart Citations